2010
DOI: 10.1007/s11250-010-9599-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine tuberculosis in Jigawa State, northwestern Nigeria

Abstract: We determined the prevalence of bovine tuberculosis in Jigawa State, northwestern Nigeria using the comparative intradermal tuberculin test in 22 herds consisting of 922 cattle with overall and individual prevalence of 1.08% (10/922) and 45.45% (10/22) obtained, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Our results corroborate those of several authors who reported that aerosols are the main route of cattle-to-cattle transmission [32][34]. Similarly, several other authors [35], [36] found a significant association between respiratory pathology and reactivity to CITT. We found that the practice of quarantine reduced the presence of animals reacting positively to CITT within herds (OR 4.2, 95% CI: 0.96–18.40, p-value = 0.056).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results corroborate those of several authors who reported that aerosols are the main route of cattle-to-cattle transmission [32][34]. Similarly, several other authors [35], [36] found a significant association between respiratory pathology and reactivity to CITT. We found that the practice of quarantine reduced the presence of animals reacting positively to CITT within herds (OR 4.2, 95% CI: 0.96–18.40, p-value = 0.056).…”
Section: Discussionsupporting
confidence: 92%
“…Our results show a significant association between the presence of animals with chronic cough and the presence of cattle in the households reacting to CITT. This suggests that the disease can be transmitted to humans through the inhalation of cough sprays from infected cattle [36]. This assertion is further sustained by Ayele et al [41] who noted that pulmonary TB due to Mycobacterium bovis is more common in rural dwellers as a result of inhalation of dust particles or bacteria-containing aerosols shed by infected animals.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The prevalence of bovine tuberculosis in Jigawa State, northwestern Nigeria using the comparative intradermal tuberculin test in 22 herds consisting of 922 cattle projected an overall and individual prevalence of 1.08% (10/922) and 45.45% (10/22), respectively [16]. A study in 2010 assessed the risk of transmission of tuberculosis through milk.…”
Section: Tuberculosismentioning
confidence: 99%
“…Reports of several workers established the existence of M. bovis in milk of animal origin (Shehu, 1988), humans (Shehu, 1988;Abubakar, 2007;Shitaye et al, 2007) and animal population (Alhaji, 1976;Ayanwele, 1984;Shehu, 1988;Dusai and Abdullahi, 1994;Shitaye et al, 2007;Okaiyeto et al, 2008;Ibrahim et al, 2010;Cadmus et al, 2004Cadmus et al, , 2010 in Nigeria.…”
Section: Bovine Tuberculosismentioning
confidence: 99%